Process for efficiently synthesizing high-pi conjugated molecule containing benzophosphopentadiene structure
By preparing magnetic composite materials and grafting polybasic acid, and preparing composite catalysts, the problems of low yields and harsh reaction conditions of the synthesis of benzophosphoheteroclopopentadiene structure in the prior art are solved, and high efficiency is achieved Synthesis and high catalytic stability.
Patent Information
- Application Number
- CN202411496110.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-07
AI Technical Summary
When synthesising benzophosphorheterocyclopentadiene structure high π conjugated molecules, the prior art faces problems such as low yield, many by-products, and harsh reaction conditions, which limits its practical application.
Magnetic composites with high specific surface area are prepared by preparing magnetic iron oxide nanoparticles and hydrothermal reaction with glucose and sodium dodecyl sulfate. Then, the polybasic acid is grafted onto a magnetic composite material to prepare a composite catalyst, and the catalyst is used to catalyze the synthesis of a high π conjugated molecule containing benzophosphorus heterocyclopentadiene structure.
The conversion rate of biphenyl phosphate is improved, the yield of high π conjugated molecules with benzophosphoheterocyclopentadiene structure is improved, and the composite catalyst still has a high conversion rate after 10 reuses.
Smart Images

Figure CN119390728A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of chemical synthesis, and in particular to a process for efficiently synthesizing high-π conjugated molecules containing a benzophosphole structure. Background Art
[0002] π-conjugated molecules have attracted much attention due to their wide applications in optoelectronic materials, organic semiconductors, dye-sensitized solar cells, organic light-emitting diodes, field-effect transistors, etc. Such molecules usually have excellent optical and electrical properties and are an important part of modern organic electronics and optoelectronic technology. The benzophosphole structure occupies a place in the π-conjugated system due to its unique electronic properties and spatial structure. Such compounds not only have good conjugation extension capabilities, but also can adjust the electronic properties of the molecule by introducing phosphorus atoms, thereby further optimizing the performance of the material.
[0003] At present, the relatively reliable scheme for synthesizing benzophosphinocyclopentadiene compounds is the intramolecular cyclization of o-alkynylaryl phosphines and the cross-coupling of brominated benzophosphinocyclopentadiene with aromatic boronic acids. Although it can achieve the synthesis of target molecules to a certain extent, it often faces problems such as low yield, many by-products, and harsh reaction conditions, which limits the practical application of such compounds.
[0004] Therefore, we proposed a process for the efficient synthesis of highly π-conjugated molecules containing benzophosphole structures to improve their yield. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention aims to provide a process for efficiently synthesizing highly π-conjugated molecules containing a benzophosphole structure.
[0006] A process for efficiently synthesizing a highly π-conjugated molecule containing a benzophospholene structure comprises the following steps:
[0007] S1: Preparation of magnetic composite materials
[0008] Dissolving ferrous sulfate heptahydrate and ferric chloride hexahydrate in deionized water, adding ammonia water and aging, separating by an external magnet, washing and drying to obtain iron oxide nanoparticles for later use, then dissolving glucose and sodium dodecyl sulfate powder in deionized water, adding iron oxide nanoparticles, uniformly dispersing, performing hydrothermal reaction, separating by an external magnet, washing and drying to obtain a magnetic composite material;
[0009] S2: Modification of magnetic composites
[0010] The magnetic composite material and 1,2,3,4-butanetetracarboxylic acid are dispersed in anhydrous ethanol, and a modification solution is added to perform a primary modification to prepare a primary modified magnetic separation composite material, and then the primary modified magnetic composite material is added to a silane coupling agent solution for a secondary modification to obtain a secondary modified magnetic composite material;
[0011] S3: Preparation of polyacids
[0012] Dissolve ammonium metatungstate dihydrate, sodium metavanadate dihydrate and sodium dihydrogen phosphate in deionized water, add sodium molybdate aqueous solution and sulfuric acid solution to adjust pH, then heat and stir to react, cool, extract and rotary evaporate to obtain polyacid;
[0013] S4: Preparation of composite catalyst
[0014] The polyacid is dissolved in deionized water, and then the secondary modified magnetic composite material is added, and ultrasonic treatment and stirring are performed, and after magnetic separation, washing and drying, a composite catalyst is obtained;
[0015] S5: Reaction preparation of highly π-conjugated molecules containing benzophosphole structure
[0016] Add biphenyl phosphate and benzenesulfonyloxyacetic acid in a molar ratio of 1:(1.2-1.4) to N,N-dimethylformamide, stir and mix thoroughly, then add the composite catalyst, heat and stir at 120-130° C. for 10-12 hours, cool naturally to room temperature, separate and recover the composite catalyst by an external permanent magnet, and purify by vacuum distillation to obtain a high π-conjugated molecule containing a benzophosphole structure;
[0017] The structural formula of biphenyl phosphate is as follows:
[0018]
[0019] The structural formula of benzenesulfonyloxyacetic acid is as follows:
[0020]
[0021] The structural formula of the high π-conjugated molecule containing benzophosphopentene structure is as follows:
[0022]
[0023] Among them, R1 and R2 are methyl, ethyl, halogen, phenyl, and methoxy.
[0024] Furthermore, S1 specifically includes the following steps:
[0025] S1.1: Add ferrous sulfate heptahydrate and ferric chloride hexahydrate into deionized water at a solid-liquid ratio of 1 g: (1.8-2.2) g: (60-70) mL, stir thoroughly to dissolve, and obtain a mixed iron solution;
[0026] S1.2: adding 25-35 wt % ammonia water to the mixed iron solution while stirring, and then standing for 1-2 hours, and then separating the formed black precipitate with an external magnet, and washing and drying the black precipitate to obtain iron oxide nanoparticles;
[0027] S1.3: Add glucose and sodium dodecyl sulfate powder into deionized water at a solid-liquid ratio of 1 g: (3-5) g: (40-50) mL, and heat and stir at 40-50 °C until completely dissolved to obtain a mixed solution;
[0028] S1.4: adding the iron oxide nanoparticles to the mixed solution, stirring for 1-2 hours, and then ultrasonically treating for 20-30 minutes to form a suspension;
[0029] S1.5: Place the above suspension in a hydrothermal reactor, heat at 180-190°C for 4-5 hours, cool naturally to room temperature, separate with an external magnet, wash and dry to obtain a magnetic composite material.
[0030] Furthermore, S2 specifically includes the following steps:
[0031] S2.1: Add the magnetic composite material prepared in step S1.5 and 1,2,3,4-butanetetracarboxylic acid into anhydrous ethanol at a solid-liquid ratio of 1 g:(8-10) g:(70-80) mL, stir and disperse thoroughly to obtain a magnetic composite material dispersion;
[0032] S2.2: Add the modified solution to the above magnetic composite material dispersion, heat and stir at 40-50°C for 8-10h to perform a primary modification, cool naturally to room temperature, filter, wash and dry to obtain a primary modified magnetic composite material;
[0033] S2.3: Mix anhydrous ethanol and deionized water in a volume ratio of (2-4):1, add hydrochloric acid to adjust the pH to 4-5, then add silane coupling agent KH-590, and stir to hydrolyze to obtain a silane coupling agent solution;
[0034] S2.4: Add the above-mentioned primary modified magnetic composite material to the above-mentioned silane coupling agent solution at a solid-liquid ratio of 1g:(15-25)mL, ultrasonically disperse for 20-30min, then heat and stir at 70-80℃ to react for 8-10h, perform secondary modification, naturally cool to room temperature, filter, wash and dry to obtain the secondary modified magnetic composite material.
[0035] Furthermore, S3 specifically includes the following steps:
[0036] S3.1: Add ammonium metatungstate dihydrate, sodium metavanadate dihydrate and sodium dihydrogen phosphate into deionized water at a solid-liquid ratio of (60-70) g: (3-4) g: 1 g: (4-5) L, stir and dissolve thoroughly to obtain a mixed aqueous solution;
[0037] S3.2: Add sodium molybdate aqueous solution to the mixed aqueous solution, and then add 50% sulfuric acid solution to adjust the pH to 2-3 to obtain a precursor solution;
[0038] S3.3: The precursor solution is heated to 70-80°C, then stirred and reacted for 3-4 hours. After naturally cooling to room temperature, it is extracted with ether, and then the ether is removed by rotary evaporation to obtain a polyacid.
[0039] Furthermore, S4 specifically includes the following steps:
[0040] S4.1: Add the polyacid prepared in step S3.3 into deionized water at a solid-liquid ratio of 1 g: (180-200) mL, stir thoroughly to dissolve, and obtain a polyacid solution;
[0041] S4.2: Add the secondary modified magnetic composite material obtained in step S2.4 to the above polyacid solution at a solid-liquid ratio of 1g:(90-100)mL, ultrasonically treat for 1-2h, and then stir for 10-12h. After magnetic separation, washing and drying, a composite catalyst is obtained.
[0042] Furthermore, the volume ratio of ammonia water to the mixed iron solution is 1:(2.8-3.4).
[0043] Furthermore, the solid-liquid ratio of the iron oxide nanoparticles to the mixed solution is 1 g: (100-120) mL.
[0044] Furthermore, the modified solution is prepared by mixing the crosslinking agent XR-100 and anhydrous ethanol in a mass ratio of 1:(20-30), and the volume ratio of the modified solution to the magnetic composite material dispersion is 1:(1-3).
[0045] Furthermore, the volume ratio of the sodium molybdate aqueous solution to the mixed aqueous solution is 1:(9-11), and the sodium molybdate aqueous solution is prepared by mixing sodium molybdate and deionized water at a solid-liquid ratio of 1g:(400-500)mL.
[0046] Furthermore, the added amount of the composite catalyst is 2-6wt% of the mass of the biphenyl phosphate.
[0047] Compared with the prior art, the present invention has at least the following beneficial effects:
[0048] 1. The present invention prepares magnetic iron oxide nanoparticles first, then uniformly disperses the nanoparticles in a solution formed by glucose and dodecyl sulfuric acid dissolved in water, performs a hydrothermal reaction, and prepares a magnetic composite material with a high specific surface area. Then, a polyacid prepared by using dihydrated ammonium metatungstate and dihydrated sodium metavanadate as raw materials is grafted onto the magnetic composite material to prepare a composite catalyst. When the composite catalyst is used to catalyze biphenyl phosphate and benzenesulfonyloxyacetic acid to synthesize a high π-conjugated molecule containing a benzophosphocyclopentadiene structure, the composite catalyst has a high selectivity for the high π-conjugated molecule containing a benzophosphocyclopentadiene structure, thereby improving the conversion rate of biphenyl phosphate and achieving the effect of improving the yield of the high π-conjugated molecule containing a benzophosphocyclopentadiene structure. Moreover, the composite catalyst still has a high conversion rate after being repeatedly used 10 times.
[0049] 2. The present invention disperses the magnetic composite material and 1,2,3,4-butanetetracarboxylic acid in anhydrous ethanol, then adds a modification solution for surface modification to enrich the carboxyl content on the surface, and then adds the modified magnetic composite material into a silane coupling agent solution for surface modification again, thereby enabling the magnetic composite material to be grafted with more polyacids, thereby increasing the acid density of the composite catalyst, and further achieving the effect of further improving the catalytic efficiency of the composite catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.
[0051] Figure 1 The process flow chart of the highly efficient synthesis of highly π-conjugated molecules containing benzophospholene structure adopted in the embodiments of the present invention is shown.
[0052] Figure 2 The following is a summary table of the catalytic efficiency and conversion rate of the composite catalysts prepared in Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0053] The following is a detailed description of a process for efficiently synthesizing a highly π-conjugated molecule containing a benzophosphole structure provided by the present invention in conjunction with the accompanying drawings and specific examples.
[0054] In the following examples, the reaction formula for the synthesis of a highly π-conjugated molecule containing a benzophosphole structure is as follows:
[0055]
[0056] Example 1
[0057] A process for efficiently synthesizing highly π-conjugated molecules containing benzophospholene structures, such as Figure 1 As shown, the following steps are included:
[0058] S1: Preparation of magnetic composite materials
[0059] S1.1: Add ferrous sulfate heptahydrate and ferric chloride hexahydrate into deionized water at a solid-liquid ratio of 1g:1.8g:60mL, stir thoroughly to dissolve, and obtain a mixed iron solution;
[0060] S1.2: adding 25 wt% ammonia water to the mixed iron solution while stirring, and then standing for aging for 1 hour, and then separating the formed black precipitate with an external magnet, and washing and drying the black precipitate to obtain iron oxide nanoparticles, wherein the volume ratio of ammonia water to the mixed iron solution is 1:2.8;
[0061] S1.3: Add glucose and sodium dodecyl sulfate powder into deionized water at a solid-liquid ratio of 1g:3g:40mL, and heat and stir at 40°C until completely dissolved to obtain a mixed solution;
[0062] S1.4: adding the iron oxide nanoparticles to the mixed solution, stirring for 1 hour, and then ultrasonically treating for 20 minutes to form a suspension, wherein the solid-liquid ratio of the iron oxide nanoparticles to the mixed solution is 1 g:100 mL;
[0063] S1.5: placing the above suspension in a hydrothermal reactor, heating at 180°C for 4 hours, cooling naturally to room temperature, separating with an external magnet, washing and drying to obtain a magnetic composite material;
[0064] S2: Modification of magnetic composites
[0065] S2.1: Add the magnetic composite material prepared in step S1.5 and 1,2,3,4-butanetetracarboxylic acid into anhydrous ethanol at a solid-liquid ratio of 1g:8g:70mL, stir and disperse them thoroughly to obtain a magnetic composite material dispersion;
[0066] S2.2: Adding a modified solution to the above-mentioned magnetic composite material dispersion, heating and stirring at 40°C for 8 hours to perform a primary modification, naturally cooling to room temperature, filtering, washing and drying to obtain a primary modified magnetic composite material, wherein the modified solution is prepared by mixing a cross-linking agent XR-100 and anhydrous ethanol in a mass ratio of 1:20, and the volume ratio of the modified solution to the magnetic composite material dispersion is 1:1;
[0067] S2.3: Mix anhydrous ethanol and deionized water in a volume ratio of 2:1, add hydrochloric acid to adjust the pH to 4-5, then add silane coupling agent KH-590, stir and hydrolyze to obtain a silane coupling agent solution;
[0068] S2.4: Add the above-mentioned primary modified magnetic composite material to the above-mentioned silane coupling agent solution at a solid-liquid ratio of 1g:15mL, ultrasonically disperse for 20min, and then heat and stir at 70°C for 8h to perform secondary modification. After naturally cooling to room temperature, filter, wash and dry to obtain a secondary modified magnetic composite material;
[0069] S3: Preparation of polyacids
[0070] S3.1: Add ammonium metatungstate dihydrate, sodium metavanadate dihydrate and sodium dihydrogen phosphate into deionized water at a solid-liquid ratio of 60g:3g:1g:4L, stir and dissolve thoroughly to obtain a mixed aqueous solution;
[0071] S3.2: adding a sodium molybdate aqueous solution to the above mixed aqueous solution, and then adding a 50% sulfuric acid solution to adjust the pH to 2 to obtain a precursor solution, wherein the volume ratio of the sodium molybdate aqueous solution to the mixed aqueous solution is 1:9, and the sodium molybdate aqueous solution is prepared by mixing sodium molybdate and deionized water at a solid-liquid ratio of 1g:400mL;
[0072] S3.3: The precursor solution is heated to 70°C, then stirred and reacted for 3 hours, cooled naturally to room temperature, extracted with ether, and then the ether is removed by rotary evaporation to obtain a polyacid;
[0073] S4: Preparation of composite catalyst
[0074] S4.1: Add the polyacid prepared in step S3.3 into deionized water at a solid-liquid ratio of 1 g:180 mL, stir and dissolve thoroughly to obtain a polyacid solution;
[0075] S4.2: Add the secondary modified magnetic composite material prepared in step S2.4 to the above polyacid solution at a solid-liquid ratio of 1g:90mL, ultrasonically treat for 1h, stir for 10h, and obtain a composite catalyst by magnetic separation, washing and drying;
[0076] S5: Reaction preparation of highly π-conjugated molecules containing benzophosphole structure
[0077] Biphenyl phosphate and benzenesulfonyloxyacetic acid are added to N,N-dimethylformamide at a molar ratio of 1:1.2, and the mixture is fully stirred. Then the composite catalyst is added, and the mixture is heated and stirred at 120°C for 10 hours. The amount of the composite catalyst added is 2wt% of the mass of the biphenyl phosphate. After naturally cooling to room temperature, the composite catalyst is separated and recovered by an external permanent magnet, and purified by vacuum distillation to obtain a high π-conjugated molecule containing a benzophosphole structure.
[0078] Example 2
[0079] A process for efficiently synthesizing highly π-conjugated molecules containing benzophospholene structures, such as Figure 1As shown, the following steps are included:
[0080] S1: Preparation of magnetic composite materials
[0081] S1.1: Add ferrous sulfate heptahydrate and ferric chloride hexahydrate into deionized water at a solid-liquid ratio of 1g:2g:65mL, stir thoroughly to dissolve, and obtain a mixed iron solution;
[0082] S1.2: adding 30 wt % ammonia water to the mixed iron solution while stirring, and then standing and aging for 1.5 h, and then separating the formed black precipitate with an external magnet, and washing and drying the black precipitate to obtain iron oxide nanoparticles, wherein the volume ratio of ammonia water to the mixed iron solution is 1:3.1;
[0083] S1.3: Add glucose and sodium dodecyl sulfate powder into deionized water at a solid-liquid ratio of 1g:4g:45mL, and heat and stir at 45°C until completely dissolved to obtain a mixed solution;
[0084] S1.4: adding the iron oxide nanoparticles to the mixed solution, stirring for 1.5 hours, and then ultrasonically treating for 25 minutes to form a suspension, wherein the solid-liquid ratio of the iron oxide nanoparticles to the mixed solution is 1 g:110 mL;
[0085] S1.5: placing the above suspension in a hydrothermal reactor, heating at 185°C for 4.5 hours, cooling naturally to room temperature, separating with an external magnet, washing and drying to obtain a magnetic composite material;
[0086] S2: Modification of magnetic composites
[0087] S2.1: Add the magnetic composite material prepared in step S1.5 and 1,2,3,4-butanetetracarboxylic acid into anhydrous ethanol at a solid-liquid ratio of 1g:9g:75mL, stir and disperse them thoroughly to obtain a magnetic composite material dispersion;
[0088] S2.2: Adding a modified solution to the above-mentioned magnetic composite material dispersion, heating and stirring at 45°C for 9 hours to perform a primary modification, naturally cooling to room temperature, filtering, washing and drying to obtain a primary modified magnetic composite material, wherein the modified solution is prepared by mixing a cross-linking agent XR-100 and anhydrous ethanol in a mass ratio of 1:25, and the volume ratio of the modified solution to the magnetic composite material dispersion is 1:2;
[0089] S2.3: Mix anhydrous ethanol and deionized water in a volume ratio of 3:1, add hydrochloric acid to adjust the pH to 4.5, then add silane coupling agent KH-590, stir and hydrolyze to obtain a silane coupling agent solution;
[0090] S2.4: Add the above-mentioned primary modified magnetic composite material to the above-mentioned silane coupling agent solution at a solid-liquid ratio of 1g:20mL, ultrasonically disperse for 25min, and then heat and stir at 75°C for 9h to perform secondary modification. After naturally cooling to room temperature, filter, wash and dry to obtain a secondary modified magnetic composite material;
[0091] S3: Preparation of polyacids
[0092] S3.1: Add ammonium metatungstate dihydrate, sodium metavanadate dihydrate and sodium dihydrogen phosphate into deionized water at a solid-liquid ratio of 65g:(3-4)g:1g:4.5L, stir and dissolve thoroughly to obtain a mixed aqueous solution;
[0093] S3.2: adding a sodium molybdate aqueous solution to the above mixed aqueous solution, and then adding a 50% sulfuric acid solution to adjust the pH to 2.5 to obtain a precursor solution, wherein the volume ratio of the sodium molybdate aqueous solution to the mixed aqueous solution is 1:10, and the sodium molybdate aqueous solution is prepared by mixing sodium molybdate and deionized water at a solid-liquid ratio of 1g:450mL;
[0094] S3.3: The precursor solution is heated to 75°C, then stirred and reacted for 3.5 hours, cooled naturally to room temperature, extracted with ether, and then the ether is removed by rotary evaporation to obtain a polyacid;
[0095] S4: Preparation of composite catalyst
[0096] S4.1: Add the polyacid prepared in step S3.3 into deionized water at a solid-liquid ratio of 1 g:190 mL, stir and dissolve thoroughly to obtain a polyacid solution;
[0097] S4.2: Add the secondary modified magnetic composite material prepared in step S2.4 to the above polyacid solution at a solid-liquid ratio of 1g:95mL, ultrasonically treat for 1.5h, stir for 11h, and obtain a composite catalyst by magnetic separation, washing and drying;
[0098] S5: Reaction preparation of highly π-conjugated molecules containing benzophosphole structure
[0099] Biphenyl phosphate and benzenesulfonyloxyacetic acid are added to N,N-dimethylformamide at a molar ratio of 1:1.3, and the mixture is fully stirred. Then the composite catalyst is added, and the mixture is heated and stirred at 125°C for 11 hours. The amount of the composite catalyst added is 4wt% of the mass of the biphenyl phosphate. After naturally cooling to room temperature, the composite catalyst is separated and recovered by an external permanent magnet, and purified by vacuum distillation to obtain a high π-conjugated molecule containing a benzophosphole structure.
[0100] Example 3
[0101] A process for efficiently synthesizing highly π-conjugated molecules containing benzophospholene structures, such as Figure 1 As shown, the following steps are included:
[0102] S1: Preparation of magnetic composite materials
[0103] S1.1: Add ferrous sulfate heptahydrate and ferric chloride hexahydrate into deionized water at a solid-liquid ratio of 1g:2.2g:70mL, stir thoroughly to dissolve, and obtain a mixed iron solution;
[0104] S1.2: adding 35 wt % ammonia water to the mixed iron solution while stirring, and then standing and aging for 2 h, and then separating the formed black precipitate with an external magnet, and washing and drying the black precipitate to obtain iron oxide nanoparticles, wherein the volume ratio of ammonia water to the mixed iron solution is 1:3.4;
[0105] S1.3: Add glucose and sodium dodecyl sulfate powder into deionized water at a solid-liquid ratio of 1g:5g:50mL, and heat and stir at 50°C until completely dissolved to obtain a mixed solution;
[0106] S1.4: adding the iron oxide nanoparticles to the mixed solution, stirring for 2 h, and then ultrasonically treating for 30 min to form a suspension, wherein the solid-liquid ratio of the iron oxide nanoparticles to the mixed solution is 1 g:120 mL;
[0107] S1.5: placing the above suspension in a hydrothermal reactor, heating at 190°C for 5 hours, cooling naturally to room temperature, separating with an external magnet, washing and drying to obtain a magnetic composite material;
[0108] S2: Modification of magnetic composites
[0109] S2.1: Add the magnetic composite material prepared in step S1.5 and 1,2,3,4-butanetetracarboxylic acid into anhydrous ethanol at a solid-liquid ratio of 1g:10g:80mL, stir and disperse them thoroughly to obtain a magnetic composite material dispersion;
[0110] S2.2: Adding a modified solution to the above-mentioned magnetic composite material dispersion, heating and stirring at 50°C for 10 hours to perform a primary modification, naturally cooling to room temperature, filtering, washing and drying to obtain a primary modified magnetic composite material, wherein the modified solution is prepared by mixing a cross-linking agent XR-100 and anhydrous ethanol in a mass ratio of 1:30, and the volume ratio of the modified solution to the magnetic composite material dispersion is 1:3;
[0111] S2.3: Mix anhydrous ethanol and deionized water in a volume ratio of 4:1, add hydrochloric acid to adjust the pH to 5, then add silane coupling agent KH-590, stir and hydrolyze to obtain a silane coupling agent solution;
[0112] S2.4: Add the above-mentioned primary modified magnetic composite material to the above-mentioned silane coupling agent solution at a solid-liquid ratio of 1g:25mL, ultrasonically disperse for 30min, and then heat and stir at 80°C for 10h to perform secondary modification. After naturally cooling to room temperature, filter, wash and dry to obtain a secondary modified magnetic composite material;
[0113] S3: Preparation of polyacids
[0114] S3.1: Add ammonium metatungstate dihydrate, sodium metavanadate dihydrate and sodium dihydrogen phosphate into deionized water at a solid-liquid ratio of 70g:4g:1g:5L, stir and dissolve thoroughly to obtain a mixed aqueous solution;
[0115] S3.2: adding a sodium molybdate aqueous solution to the mixed aqueous solution, and then adding a 50% sulfuric acid solution to adjust the pH to 3 to obtain a precursor solution, wherein the volume ratio of the sodium molybdate aqueous solution to the mixed aqueous solution is 1:11, and the sodium molybdate aqueous solution is prepared by mixing sodium molybdate and deionized water at a solid-liquid ratio of 1g:500mL;
[0116] S3.3: The precursor solution is heated to 80°C, then stirred and reacted for 4 hours, cooled naturally to room temperature, extracted with ether, and then the ether is removed by rotary evaporation to obtain a polyacid;
[0117] S4: Preparation of composite catalyst
[0118] S4.1: Add the polyacid prepared in step S3.3 into deionized water at a solid-liquid ratio of 1 g:200 mL, stir and dissolve thoroughly to obtain a polyacid solution;
[0119] S4.2: Add the secondary modified magnetic composite material obtained in step S2.4 to the above polyacid solution at a solid-liquid ratio of 1g:100mL, ultrasonically treat for 2h, stir for 12h, and obtain a composite catalyst by magnetic separation, washing and drying;
[0120] S5: Reaction preparation of highly π-conjugated molecules containing benzophosphole structure
[0121] Biphenyl phosphate and benzenesulfonyloxyacetic acid are added to N,N-dimethylformamide at a molar ratio of 1:1.4, and the mixture is fully stirred. Then the composite catalyst is added, and the mixture is heated and stirred at 130°C for 12 hours. The amount of the composite catalyst added is 6wt% of the mass of the biphenyl phosphate. After naturally cooling to room temperature, the composite catalyst is separated and recovered by an external permanent magnet, and purified by vacuum distillation to obtain a high π-conjugated molecule containing a benzophosphole structure.
[0122] Product analysis:
[0123] The high π-conjugated molecules containing benzophosphopentene structure obtained in Examples 1-3 were analyzed by gas chromatography to calculate the conversion rate of biphenyl phosphate and the selectivity of the high π-conjugated molecules containing benzophosphopentene structure. The results are as follows: Figure 2 shown.
[0124] from Figure 2 It can be seen that when the composite catalysts prepared in Examples 1, 2 and 3 catalyze biphenyl phosphate and benzenesulfonyloxyacetic acid to synthesize high π-conjugated molecules containing benzophosphocyclopentadiene structure, the conversion rate of biphenyl phosphate and the selectivity of high π-conjugated molecules containing benzophosphocyclopentadiene structure are 92.6%, 91.8%, 92.2% and 82.3%, 81.7%, 81.9%, respectively. Moreover, after being reused 10 times, the conversion rates of the composite catalysts are 83.9%, 83.2% and 82.8%, respectively. It can be seen that by first preparing magnetic iron oxide nanoparticles and then uniformly dispersing them in glucose and dodecyl sulfuric acid dissolved in water, the conversion rate of the composite catalyst is 83.9%, 83.2% and 82.8%, respectively. A hydrothermal reaction is carried out in the formed solution to prepare a magnetic composite material with a high specific surface area, and then a polyacid prepared by using dihydrated ammonium metatungstate and dihydrated sodium metavanadate as raw materials is grafted onto the magnetic composite material to prepare a composite catalyst. When the composite catalyst is used to catalyze biphenyl phosphate and benzenesulfonyloxyacetic acid to synthesize high π-conjugated molecules containing a benzophosphocyclopentadiene structure, the composite catalyst has high selectivity for the high π-conjugated molecules containing a benzophosphocyclopentadiene structure, thereby improving the conversion rate of biphenyl phosphate and achieving the effect of improving the yield of high π-conjugated molecules containing a benzophosphocyclopentadiene structure. Moreover, the composite catalyst still has a high conversion rate after being repeatedly used 10 times.
[0125] Comparative Example 1
[0126] The difference between this comparative example 1 and Example 1 is that step S2 is removed and the secondary modified magnetic composite material in step S4 is replaced by an equal amount of magnetic composite material, that is, the magnetic composite material is not modified, and then the high π-conjugated molecule containing benzophosphole structure is synthesized according to the steps in Example 1. The results are shown in Table 1.
[0127] Comparative Example 2
[0128] The difference between this comparative example 2 and example 1 is that the step of performing one modification using a modification solution in step S2 is removed, that is, the magnetic composite material is modified only by using a silane coupling agent solution, and then a high π-conjugated molecule containing a benzophosphole structure is synthesized according to the steps in example 1. The results are shown in Table 1.
[0129] Comparative Example 3
[0130] The difference between this comparative example 3 and Example 1 is that the step of performing secondary modification using a silane coupling agent solution in step S2 is removed, that is, the magnetic composite material is modified only by using a modification solution, and then a high π-conjugated molecule containing a benzophosphole structure is synthesized according to the steps in Example 1. The results are shown in Table 1.
[0131] Table 1: Summary of conversion and selectivity results of Comparative Examples 1-3 and Example 1
[0132]
[0133]
[0134] As can be seen from Table 1, when the composite catalysts prepared in Comparative Examples 1, 2 and 3 catalyze biphenyl phosphate and benzenesulfonyloxyacetic acid to synthesize high π-conjugated molecules containing benzophosphocyclopentadiene structure, the conversion rate of biphenyl phosphate and the selectivity of high π-conjugated molecules containing benzophosphocyclopentadiene structure are 88.2%, 85.7%, 86.5% and 79.7%, 75.3%, 77.2%, respectively, which are all lower than those in Example 1. It can be seen that by first dispersing the magnetic composite material and 1,2,3,4-butanetetracarboxylic acid in anhydrous ethanol, then adding a modification solution for surface modification to enrich the carboxyl content on its surface, and then adding the once modified magnetic composite material to a silane coupling agent solution, and performing surface modification again, the magnetic composite material can be grafted with more polyacids, thereby increasing the acid density of the composite catalyst, thereby further improving the catalytic efficiency of the composite catalyst.
[0135] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A process for efficiently synthesizing highly π-conjugated molecules containing benzophosphole structure, characterized in that: The steps include: S1: Preparation of magnetic composite materials Dissolving ferrous sulfate heptahydrate and ferric chloride hexahydrate in deionized water, adding ammonia water and aging, separating by an external magnet, washing and drying to obtain iron oxide nanoparticles for later use, then dissolving glucose and sodium dodecyl sulfate powder in deionized water, adding iron oxide nanoparticles, uniformly dispersing, performing hydrothermal reaction, separating by an external magnet, washing and drying to obtain a magnetic composite material; S2: Modification of magnetic composites The magnetic composite material and 1,2,3,4-butanetetracarboxylic acid are dispersed in anhydrous ethanol, and a modification solution is added to perform a primary modification to prepare a primary modified magnetic separation composite material, and then the primary modified magnetic composite material is added to a silane coupling agent solution for a secondary modification to obtain a secondary modified magnetic composite material; S3: Preparation of polyacids Dissolve ammonium metatungstate dihydrate, sodium metavanadate dihydrate and sodium dihydrogen phosphate in deionized water, add sodium molybdate aqueous solution and sulfuric acid solution to adjust pH, then heat and stir to react, cool, extract and rotary evaporate to obtain polyacid; S4: Preparation of composite catalyst The polyacid is dissolved in deionized water, and then the secondary modified magnetic composite material is added, and ultrasonic treatment and stirring are performed, and after magnetic separation, washing and drying, a composite catalyst is obtained; S5: Reaction preparation of highly π-conjugated molecules containing benzophosphole structure Add biphenyl phosphate and benzenesulfonyloxyacetic acid in a molar ratio of 1:(1.2-1.4) to N,N-dimethylformamide, stir and mix thoroughly, then add the composite catalyst, heat and stir at 120-130° C. for 10-12 hours, cool naturally to room temperature, separate and recover the composite catalyst by an external permanent magnet, and purify by vacuum distillation to obtain a high π-conjugated molecule containing a benzophosphole structure; The structural formula of biphenyl phosphate is as follows: The structural formula of benzenesulfonyloxyacetic acid is as follows: The structural formula of the high π-conjugated molecule containing benzophosphopentene structure is as follows: Among them, R1 and R2 are methyl, ethyl, halogen, phenyl, and methoxy.
2. A process for efficiently synthesizing highly π-conjugated molecules containing benzophosphole structure according to claim 1, characterized in that: S1 specifically includes the following steps: S1.1: Add ferrous sulfate heptahydrate and ferric chloride hexahydrate into deionized water at a solid-liquid ratio of 1 g: (1.8-2.2) g: (60-70) mL, stir thoroughly to dissolve, and obtain a mixed iron solution; S1.2: adding 25-35 wt % ammonia water to the mixed iron solution while stirring, and then standing for 1-2 hours, and then separating the formed black precipitate with an external magnet, and washing and drying the black precipitate to obtain iron oxide nanoparticles; S1.3: Add glucose and sodium dodecyl sulfate powder into deionized water at a solid-liquid ratio of 1 g: (3-5) g: (40-50) mL, and heat and stir at 40-50 °C until completely dissolved to obtain a mixed solution; S1.4: adding the iron oxide nanoparticles to the mixed solution, stirring for 1-2 hours, and then ultrasonically treating for 20-30 minutes to form a suspension; S1.5: Place the above suspension in a hydrothermal reactor, heat at 180-190°C for 4-5 hours, cool naturally to room temperature, separate with an external magnet, wash and dry to obtain a magnetic composite material.
3. A process for efficiently synthesizing highly π-conjugated molecules containing benzophospholene structure according to claim 2, characterized in that: S2 specifically includes the following steps: S2.1: Add the magnetic composite material prepared in step S1.5 and 1,2,3,4-butanetetracarboxylic acid into anhydrous ethanol at a solid-liquid ratio of 1 g:(8-10) g:(70-80) mL, stir and disperse thoroughly to obtain a magnetic composite material dispersion; S2.2: Add the modified solution to the above magnetic composite material dispersion, heat and stir at 40-50°C for 8-10h to perform a primary modification, cool naturally to room temperature, filter, wash and dry to obtain a primary modified magnetic composite material; S2.3: Mix anhydrous ethanol and deionized water in a volume ratio of (2-4):1, add hydrochloric acid to adjust the pH to 4-5, then add silane coupling agent KH-590, and stir to hydrolyze to obtain a silane coupling agent solution; S2.4: Add the above-mentioned primary modified magnetic composite material to the above-mentioned silane coupling agent solution at a solid-liquid ratio of 1g:(15-25)mL, ultrasonically disperse for 20-30min, then heat and stir at 70-80℃ to react for 8-10h, perform secondary modification, naturally cool to room temperature, filter, wash and dry to obtain the secondary modified magnetic composite material.
4. A process for efficiently synthesizing highly π-conjugated molecules containing benzophospholene structure according to claim 3, characterized in that: S3 specifically includes the following steps: S3.1: Add ammonium metatungstate dihydrate, sodium metavanadate dihydrate and sodium dihydrogen phosphate into deionized water at a solid-liquid ratio of (60-70) g: (3-4) g: 1 g: (4-5) L, stir and dissolve thoroughly to obtain a mixed aqueous solution; S3.2: Add sodium molybdate aqueous solution to the mixed aqueous solution, and then add 50% sulfuric acid solution to adjust the pH to 2-3 to obtain a precursor solution; S3.3: The precursor solution is heated to 70-80°C, then stirred and reacted for 3-4 hours. After naturally cooling to room temperature, it is extracted with ether, and then the ether is removed by rotary evaporation to obtain a polyacid.
5. A process for efficiently synthesizing highly π-conjugated molecules containing benzophospholene structure according to claim 4, characterized in that: S4 specifically includes the following steps: S4.1: Add the polyacid prepared in step S3.3 into deionized water at a solid-liquid ratio of 1 g: (180-200) mL, stir thoroughly to dissolve, and obtain a polyacid solution; S4.2: Add the secondary modified magnetic composite material obtained in step S2.4 to the above polyacid solution at a solid-liquid ratio of 1g:(90-100)mL, ultrasonically treat for 1-2h, and then stir for 10-12h. After magnetic separation, washing and drying, a composite catalyst is obtained.
6. A process for efficiently synthesizing highly π-conjugated molecules containing benzophospholene structure according to claim 2, characterized in that: The volume ratio of ammonia water to mixed iron solution is 1:(2.8-3.4).
7. A process for efficiently synthesizing highly π-conjugated molecules containing benzophospholene structure according to claim 2, characterized in that: The solid-liquid ratio of the iron oxide nanoparticles to the mixed solution is 1 g: (100-120) mL.
8. A process for efficiently synthesizing highly π-conjugated molecules containing benzophospholene structure according to claim 3, characterized in that: The modified solution is composed of crosslinker XR-100 and anhydrous ethanol in a mass ratio of 1: (20-30) and the volume ratio of the modified solution to the magnetic composite material dispersion is 1: (1-3)。 9. A process for efficiently synthesizing highly π-conjugated molecules containing benzophospholene structure according to claim 4, characterized in that: The volume ratio of the sodium molybdate aqueous solution to the mixed aqueous solution is 1:(9-11), and the sodium molybdate aqueous solution is prepared by mixing sodium molybdate and deionized water at a solid-liquid ratio of 1g:(400-500)mL.
10. The process for efficiently synthesizing highly π-conjugated molecules containing benzophospholene structure according to claim 1, characterized in that: The added amount of the composite catalyst is 2-6wt% of the mass of the biphenyl phosphate.